Ready Biodegradability Ring Testing of 4‐Isopropylphenol in Different Laboratories for Critical Evaluation of a Biodegradable Reference Substance. (1st December 2020) - Gu, Wen; Zhou, Linjun; Wang, Zhen; Lin, Chunjun; Liu, Jining; Ge, Haihong; Shi, Lili
ABSTRACT: Ready biodegradability is a key property for studying the environmental and ecological risks posed by chemicals, and a reference substance is used to check the reliability of the test results. Traditional reference substances such as aniline, sodium benzoate, and ammonium acetate rapidly degrade even in test systems without inoculum. In this study, 4‐isopropylphenol was investigated as a reference candidate. Aerobic biodegradation of 4‐isopropylphenol was studied using different methods, and repeatability tests were performed in multiple laboratories. 4‐Isopropylphenol met the ready biodegradability passing level in a closed bottle test (OECD 301D) and manometric respirometry test (OECD 301F). No obvious toxicity was found in activated sludge respiration inhibition and biodegradable toxicity control tests. The results of 301F tests performed in 15 Chinese laboratories were compared using statistical robustness analyses and Z ‐scores. The robust average 28‐d biodegradability rate for 4‐isopropylphenol was 80.3%, and the relative standard deviation was 9.20%. The data from the 15 laboratories consistently indicated that 4‐isopropylphenol was readily biodegradable, except for an "unsatisfactory" outlier result from 1 laboratory. The degradation kinetics of 4‐isopropylphenol were derived from a logistic model, which had a good fit for the degradation curve. The biodegradation lag phase was 2.3 d (range 2–5 d), and the pass level was attained at 6.5 d on average (range 2–9 d), which met the 10‐d window requirement. The biodegradation rate at 28 d was 75.3% (range 64.0%–95.1%). The ready biodegradability of 4‐isopropylphenol indicates that it will be more appropriate as a reference chemical than other reference compounds used for investigating the biodegradability of chemicals. Integr Environ Assess Manag 2021;17:562–572. © 2020 SETAC KEY POINTS: Provided critical assessment for the improvement of the best practices when conducting biodegradable studies globally due to regulatory and product stewardship drivers. Provide sufficient ring test data for the evaluation of new potential biodegradable reference material 4‐isopropylphenol.